2018
DOI: 10.1177/0269215518788598
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of vestibular rehabilitation and head-mounted gaming task procedure in unilateral vestibular hypofunction: a 12-month follow-up of a randomized controlled trial

Abstract: Results suggest that head-mounted gaming home exercises are a viable, effective, additional measure to improve long-term vestibular rehabilitation outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 35 publications
3
51
1
10
Order By: Relevance
“…Los pacientes tratados mejoraron su control direccional y su balanceo, especialmente en las primeras fases de la enfermedad [27]. Viziano et al (2018), estudiaron los efectos a largo plazo de la rehabilitación vestibular con HMD. De los 47 pacientes con hipofunción vestibular unilateral, a 24 se le administró una terapia vestibular convencional y a 23 con gafas de realidad virtual durante un mes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los pacientes tratados mejoraron su control direccional y su balanceo, especialmente en las primeras fases de la enfermedad [27]. Viziano et al (2018), estudiaron los efectos a largo plazo de la rehabilitación vestibular con HMD. De los 47 pacientes con hipofunción vestibular unilateral, a 24 se le administró una terapia vestibular convencional y a 23 con gafas de realidad virtual durante un mes.…”
Section: Discussionunclassified
“…De los 47 pacientes con hipofunción vestibular unilateral, a 24 se le administró una terapia vestibular convencional y a 23 con gafas de realidad virtual durante un mes. Este último grupo mejoró significativamente al año, tanto en la ganancia como en los parámetros posturográficos [28].…”
Section: Discussionunclassified
“…Less is known about possible variations in longterm rehabilitation outcomes; to this regard, it is of relevance that patients who were treated with HMDbased exercises maintained improvements in VOR gain and self-report measures as far as 12 months after discontinuation [7]. Such experiences seem to confirm that patient-tailored, VR-based vestibular rehabilitation may induce long-lasting adaptations in the central nervous system and that patients can remain free of symptoms after long periods of time.…”
mentioning
confidence: 89%
“…Video-games that require whole-body physical activity to play the game combine motor and cognitive exercises and are labeled Exergames ( 25 ). Exergames provide a motivational and entertaining way to be physically active for patients ( 12 , 26 ), and recent studies demonstrated a positive effect of virtual reality-based interventions on patients with vestibular hypofunction ( 27 29 ). This form of training theoretically allows addressing all four important exercise components for vestibular subjects ( 11 ) into one exercise program: gaze stability exercises and habituation exercises ( 24 ), balance and gait exercises ( 30 , 31 ), and endurance ( 32 ).…”
Section: Introductionmentioning
confidence: 99%